Analisis Performance Jangka Pendek Pembangkit Listrik Tenaga Surya dengan Sistem Stand-alone System - Rhezal Agung Ananto; Asfari Hariz Santoso (Elposys: Jurnal Sistem Kelistrikan, 2021)
Renewable energy power generation technology continues to develop every year and energy demand continues toincrease. Reducing carbon emissions in accordance with international carbon emission policies (including Indonesia). The renewable energy target is targeted to increase every year in accordance with the national renewable energy mix policy. Renewable energy has characteristics that fluctuate over time, so continuous measurement data is needed. This data is used for the design of renewable energy in Indonesia in the future. To analyze the performance of a solar power plant, measurement variables are needed. Photovoltaic analysis requires measurement of variable voltage, current, power and energy. Measurement variables are measurement variables from photovoltaic and measurement variables from solar energy. The measurement of solar energy is measured in Watts per square meter. The measurement method is a direct measurement in the territory of Indonesia. The measurement method is the measurement at sunrise to sunset. The measurement results are used for performance analysis. The measurements result are used for photovoltaic efficiency analysis.